Root and shoot hydraulic conductance of seven Quercus species - Nardini, Andrea; Tyree T., Melvin (Ann. For. Sci., 1999)
The root (KR) and shoot (KS) hydraulic conductances of seven different Quercus species, as well as the leaf blade hydraulic resistance (RLL), were measured in potted plants with the aim of understanding whether a relationship exists between the hydraulic architecture and the general ecological behaviour of different species of this genus. The KR values were scaled by dividing by root surface area (KRR) and by leaf surface area (KRL) and the KS values were scaled by dividing by leaf surface area (KSL). The likely drought-adapted species (Quercus suber, Q. pubescens, Q. petraea) showed lower KRL and KRR, lower KSL and higher RLL with respect to the known water-demanding species (Q. alba, Q. cerris, Q. robur, Q. rubra). The possible physiological and ecological significance of such differences are discussed.
Keywords: high pressure flow meter; leaf blade resistance; Quercus; Root hydraulic conductance; shoot hydraulic conductance